Methodological Variations Contributing to Heterogenous Ergogenic Responses to Ischemic Preconditioning - O'Brien, Liam; Jacobs, Ira (Frontiers in Physiology, 2021)
Ischemic preconditioning (IPC) has been demonstrated to augment maximal exercise performance over a range of exercise durations and modalities. However, the reproducibility and robustness of ergogenic responses to this technique vary substantially across the literature, confounding expectations about the magnitude of its effects. Considerable variability between study methodologies, and the possible existence of IPC non-responders have been previously hypothesized to be responsible for the heterogenous response to IPC. This review article summarizes current knowledge of the ergogenic evidence and the likely mediating mechanisms and aims to identify the potential sources for the reported variations in response to IPC. We propose several avenues for future investigation including the existence of non-responders, sex-based differences in response, and the development of clearer methodological guidelines for IPC interventions involving exercise